Understanding conflict-related sexual violence and the 'everyday' experience of conflict through witness testimonies. (June 2019) - Campbell, Kirsten; Demir, Elma; O'Reilly, Maria
The testimonies of witnesses who testify before criminal courts provide crucial insights into the situated experience of conflict-related sexual violence. Witness testimonies highlight the complex realities and everyday lives of individuals caught up in situations of armed conflict. The evidence presented by witnesses can provide vital insights into lived experiences of wartime violence, and reveal the seemingly mundane strategies and tactics adopted by victims to cope with, survive and resist the violent and coercive circumstances of war. This article foregrounds conflict-related sexual violence witness testimonies as highly significant sources of knowledge of everyday experiences of conflict. It sets out a bottom-up, mixed-method approach for identifying and analysing the experiential accounts of those who lived through conflict-related sexual violence, while engaging with the opportunities and challenges of using witness testimony. Our approach unsettles existing notions of 'the everyday' in Peace & Conflict Studies as a synonym for narratives and practices of violence, justice and peacebuilding that are private, informal and largely hidden from view. Understanding witness testimonies requires conceptualising the everyday as an amalgam of formal and informal practices, as accessible through both elite and lay knowledges and as documented in both public and private (e.g. redacted) sources. It requires challenging taken-for-granted dichotomies that are frequently invoked to understand conflict and peace.